Lithosyntrophy: Obligate syntrophy in a phosphite-oxidizing, methanogenic culture - Heidi S. Aronson; Matt E. Weaver; Ruiwen Hu; V. Celeste Lanclos; Jacob D. Rapp; Anthony T. Iavarone; Hans K. Carlson; John D. Coates (Proceedings of the National Academy of Sciences, 2026)
The anaerobic conversion of organic matter to methane and carbon dioxide typically relies on obligate syntrophic interactions between bacteria and methanogenic archaea, where interspecies electron transfer enables thermodynamically constrained reactions to proceed near equilibrium. Syntrophs often couple the oxidation of fermentation products such as fatty acids and alcohols to the reduction of protons to form hydrogen (H 2 ). These reactions can only proceed if low H 2 concentrations are maintained by H 2 -consuming syntrophic partners. Here, we describe “lithosyntrophy,” a mode of syntrophic interaction in which electrons that drive hydrogenotrophic methanogenesis originate from an inorganic compound rather than from the canonical organic substrates. Candidatus Phosphitivorax anaerolimi Phox-21 oxidizes phosphite (HPO 3 2− , oxidation state +3) to phosphate coupled to hydrogenogenesis in an obligate energetic dependency on a hydrogenotrophic methanogen, Methanoculleus sp. Physiology experiments, thermodynamic calculations, genomic annotation, and metaproteomics analysis collectively revealed a mechanism for syntrophic phosphite oxidation in Phox-21. In this pathway, electrons derived from phosphite drive H 2 production via an electron-confurcating hydrogenase. Unlike previously characterized acetogenic phosphite oxidizers, Phox-21 is a mixotroph that assimilates acetate to form biomass. Lithosyntrophic phosphite oxidizers may play important roles both in transferring reducing equivalents as well as biologically available phosphorus to other members of their surrounding microbial communities, establishing a previously unrecognized metabolic and biogeochemical link between the phosphorus and carbon redox cycles in anoxic ecosystems.